Dlg1 deletion in microglia ameliorates chronic restraint stress induced mice depression-like behavior - Xiaoheng Li; Zhixin Peng; Lingling Jiang; Lingling Jiang; Ping Zhang; Ping Zhang; Pin Yang; Pin Yang; Zengqiang Yuan; Jinbo Cheng; Jinbo Cheng (Frontiers Media S.A., 2023)
Background: Major depression is one of the most common psychiatric disorders worldwide, inflicting suffering, significant reduction in life span, and financial burdens on families and society. Mounting evidence implicates that exposure to chronic stress can induce the dysregulation of the immune system, and the activation of brain-resident innate immune cells, microglia, leading to depression-like symptoms. However, the specific mechanisms need to be further elucidated.Method: Animal models of depression were established by chronic restraint stress (CRS), and depression-like behavior was assessed by sucrose preference test (SPT), open field test (OFT), tail suspension test (TST) and forced swimming test (FST). Microglial activation was visualized by immunofluorescent and immunohistochemical staining, and microglial morphological changes were further analyzed by skeleton analysis. The levels of inflammatory cytokines were detected by western blotting and qPCR.Result: Microglial Dlg1 knockout ameliorates CRS-induced mice depression-like behavior. In contrast to the effect of Dlg1 in the LPS-induced mouse model, Dlg1 knockout had little effect on microglial density, but significantly decreased the number of activated microglia and reversed microglia morphological changes in mice challenged with CRS. Moreover, the upregulation of inflammatory cytokines following CRS exposure was partially reversed by Dlg1 deletion.Conclusion: Our study provides the evidence that Dlg1 ablation in microglia remarkedly reverses microglial activation and depression-like behavior in mice exposed to CRS, implicating a potential target for the treatment of clinical depression.